2009
DOI: 10.1136/bmj.b2810
|View full text |Cite
|
Sign up to set email alerts
|

ExStroke Pilot Trial of the effect of repeated instructions to improve physical activity after ischaemic stroke: a multinational randomised controlled clinical trial

Abstract: Objectives To investigate if repeated verbal instructions about physical activity to patients with ischaemic stroke could increase long term physical activity.Design Multicentre, multinational, randomised clinical trial with masked outcome assessment.Setting Stroke units in Denmark, China, Poland, and Estonia.Participants 314 patients with ischaemic stroke aged ≥40 years who were able to walk—157 (mean age 69.7 years) randomised to the intervention, 157 (mean age 69.4 years) in the control group.Interventions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
108
1
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 107 publications
(118 citation statements)
references
References 35 publications
2
108
1
2
Order By: Relevance
“…Three studies reported on recurrent stroke or TIA events [36, 41,44]. Although in all three studies there were no differences between the groups, recurrent event rate was not the primary objective of the studies, nor were they powered for this variable.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Three studies reported on recurrent stroke or TIA events [36, 41,44]. Although in all three studies there were no differences between the groups, recurrent event rate was not the primary objective of the studies, nor were they powered for this variable.…”
Section: Resultsmentioning
confidence: 99%
“…The number of techniques used in each of the 14 interventions ranged between two and six (median of three techniques). The duration and number of sessions ranged between 2 weeks [37] and 24 months [44], and 2 [37, 40] to 13 [42] sessions, respectively. The mean length of each individual session ranged between 38.5 and 73 minutes.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations